Centrifuge modelling of discrete pile rows to stabilise slopes - Yoon, Boung Shik (2008)
Discrete pile rows are widely used for improving the stability of potentially unstable slopes, where columns of reinforced concrete are constructed in the ground to reinforce it and inhibit instability. The method becomes more cost effective with wider pile spacings, but simultaneously there is also increasing risk that the soil will flow through the gap between adjacent piles, rather than arching across it. The impact of pile spacing along the row, which is likely to have a significant effect on stability, is not clearly understood from a current design perspective. In this study the effects of pile spacing on passive interaction with the slope are investigated using a series of geotechnical centrifuge model tests which are interpreted with a proposed theoretical framework.